Profile of Internet Cafe users in Turkey - Gürol, Mehmet; Sevindik, Tuncay (My University, 2007)
It is a fact that, Internet Cafes are the sign of information community. Internet cafes functions as a bridge between the people cannot be aware of the latest events or technological developments due to economical reasons, and cyber world. This study was carried out to show the profile of users Internet Cafe in Turkey. Description hatching model is used in the research. In Elazi{dotless}?/Turkey, the number of the Internet Cafes, having computer game is 10 and the number of other Internet Cafes having no computer games are 16. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Digital; Internet; Internet Cafe